The Problem and Need for Continuing Professional Development of Vocational School Teachers - Tri Murwaningsih; Muna Fauziah (Jurnal Pendidikan Teknologi dan Kejuruan, 2022)
This study aims to analyze the problems and the needs of vocational school teachers in the implementation of continuing professional development. This research is qualitative. This study’s sample was 120 vocational school teachers in Surakarta Residency, Indonesia. A questionnaire, interview, and documentation instruments were used in this study. A triangulation technique was employed to validate research instruments, while interactive analysis was utilized to analyze research data with stages data reduction, data presentation, and drawing conclusions. This research produced two pieces of information. First, the problems that occurred during the implementation of the continuing professional development program included: training activities had not been carried out according to teacher expectations; material was not suitable to the program; the trainer was inadequate in delivering the material; training was still carried out on weekdays; a large amount of administrative burden on teachers; low financial support; age; and teachers' lack of interest and insight about scientific work. Second, there were three aspects of the teachers’ needs in the CPD program: self-development (variations in training to improve teacher abilities), aspects of scientific publications (writing scientific papers to journal publications), and aspects of innovative work (book development, teaching aids, learning innovations, etc.).